Deep Carbon 2019
DOI: 10.1017/9781108677950.012
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nanoporosity on the Behavior of Carbon-Bearing Fluids

Abstract: david cole and alberto striolo IntroductionPorosity and permeability are key variables linking the origin, form, movement, and quantity of carbon-bearing fluids that collectively dictate the physical and chemical evolution of fluid-gas-rock systems. 1 The distribution of pores, pore volume, and their connectedness vary widely, depending on the Earth material, its geologic context, and its history. The general tendency is for porosity and permeability to decrease with increasing depth, along with pore size and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 147 publications
1
6
0
Order By: Relevance
“…We note that in our experiments, confined propane remains in the vapor phase even at the lower temperatures probed. The effect of confinement due to the MCM-41-S pores seems to correspond to an increase in pressure, which would imply an increase in density for the confined fluid, consistent with many simulation results 47 .…”
Section: Discussionsupporting
confidence: 88%
“…We note that in our experiments, confined propane remains in the vapor phase even at the lower temperatures probed. The effect of confinement due to the MCM-41-S pores seems to correspond to an increase in pressure, which would imply an increase in density for the confined fluid, consistent with many simulation results 47 .…”
Section: Discussionsupporting
confidence: 88%
“…Due to the significantly small scale of the pores often found in shale formations, but also in engineering materials such as catalysts, atomistic molecular dynamics and Monte Carlo simulations (MD and MC) have been widely used to quantify fluid transport through narrow pores as well as fluid structure and preferential adsorption. 18 The atomistic simulations allow the user to define 1) the chemical composition of the pores, 2) their shape and size, 3) the fluids and mixtures that fill the pores, and 4) conditions such as temperature and pressure. For example, Sui et al studied adsorption and transport of methane in dry and water-wet montmorillonite clays and found that the methane self-diffusion coefficient increases rapidly as the pore size increases.…”
Section: Introductionmentioning
confidence: 99%
“…9 For these strategies to be fully optimised, it is important to understand, and ultimately control the molecular mechanisms that are responsible for rock-fluid interactions, inclusive of fluid sorption, migration, and fixation. 10 We consider here enhanced oil recovery (EOR). EOR methods commonly used include water, gas, and surfactant injection.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 injection into geological formations has received much attention, sometimes as a long-term storage opportunity, whereas in some other cases, CO 2 has been injected in oil and gas fields to attempt to simultaneously achieve enhanced hydrocarbon recovery and CO 2 sequestration . For these strategies to be fully optimized, it is important to understand and ultimately control the molecular mechanisms that are responsible for rock–fluid interactions, inclusive of fluid sorption, migration, and fixation …”
Section: Introductionmentioning
confidence: 99%